PEMBAURAN ETNIS TIONGHOA DAN GORONTALO PADA SEKTOR EKONOMI DITINJAU DALAM PERSPEKTIF SEJARAH - Resmiyati Yunus (Jambura History and Culture Journal, 2019)
This Gorontalo is one of regions with varied inhabitants, particularly if it is reviewed from the ethnic aspect. Instead of indigenous people who are ethnic Gorontalo, there are other ethnic classified as comers too, including ethnic Chinese. The attendance of the Ethnic Chinese in Biawao Village of Gorontalo City was began in second half of 19 Century (1856) and intensively since early of 20 Century along with direct administration applied by Dutch Colonial over Gorontalo region. Their presence in Gorontalo and Indonesia was commonly driven by frequent problem emerged in China which was not enabling them to have a better life. In addition, hope for fate improvement offered by new land also became a trigger of Chinese migration to all over the world including Gorontalo. as time went by, the ethnic Chinese in Gorontalo had assimilated with local inhabitant (ethnic Gorontalo), and it occurred thorough several interactive media which the most dominant were tradevand marriage.